Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.